The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1413-785220172502165651
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries Among Amateur Athletes at a Brazilian University

Abstract: Objective: To obtain information on the incidence and nature of sports injuries at a Brazilian university.Method: Data from 396 student amateur athletes (61% male) playing 15 different sports during the 2013 season were retrospectively evaluated. Subjects completed the National Collegiate Athletic Association Injury Surveillance System questionnaire at the conclusion of the 2013 sports season. Injuries that resulted in at least one day of time lost were included. Exposure was defined as one student amateur ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…As recreational athletic activities become popular, ACL injuries on an annual basis have increased. 15,16 It has been shown that most patients develop osteoarthritis of the knee 15 to 20 years after an ACL injury, regardless of the treatment. 17,18 Moreover, most individuals require reconstruction of the ACL, which leads to a long rehabilitation and absenteeism from work.…”
Section: Discussionmentioning
confidence: 99%
“…As recreational athletic activities become popular, ACL injuries on an annual basis have increased. 15,16 It has been shown that most patients develop osteoarthritis of the knee 15 to 20 years after an ACL injury, regardless of the treatment. 17,18 Moreover, most individuals require reconstruction of the ACL, which leads to a long rehabilitation and absenteeism from work.…”
Section: Discussionmentioning
confidence: 99%
“…Contact sports are those in which participants establish direct physical contact with other players or objects, resulting in greater likelihood of trauma and injuries . Dento‐alveolar injuries such as tooth avulsion, fracture, subluxation, and intrusion demonstrate a significant prevalence in recent studies .…”
Section: Introductionmentioning
confidence: 99%
“…The present study reported an injury rate of 9.9 per 1000 S-E. The highest injury rate was in badminton, which recorded 13.8 per 1000 S-E. Asperti, Fernandes, Pedrinelli, and Hernandez (2017) reported that injury rates among amateur athletes at a Brazilian university to be 13 per 1000 athlete-exposure (A-E). A report from 16 years of the National Collegiate Athletic Association (NCAA) injury surveillance found an injury rate of 13.8 per 1000 athlete-exposure, with football having the highest risk (Hootman, Dick, & Agel, 2007).…”
Section: Discussionmentioning
confidence: 44%